THE CATASTROPHE SCENARIO OF THE UNITES NATIONS’ IPCC AND INTERNATIONAL POLITICAL ECONOMY - Murat GÜL (Fırat University, 2019)
Following long political discussions, UN World Climate Council approved the “Climate Change 2007” Report. This report sets forth that the world will face scenario catastrophe due to the global warming. According to this report, in the next 50 years approximate it is expected that global temperature will rise by 1,5 to 2,5 degrees, if this occurs about 20-30% of plant and animal species will diminish and due to this chain of developments human life may encounter a serious threat. On the other hand, there is a similar scenario for the natural resources: According to the forecasts of the US Ministry of Energy, even if the world oil consumption increases 2% by year, the proved oil resources may run out within 30 years. The data provided bring out the necessity to construct a comprehensive perspective over political and economic problems in the world. This study seeks to make an overall assessment on international political economy within the framework of the main issues and main approaches. In order to identify the main issues and perspectives, the statistical data regarding the basic energy resources (oil and natural gas) will be used. It is argued here that natural resources play an important role related to political and economic problems in the world. The reason behind its becoming a popular approach (again) during the 1970s can be explained through oil crisis and the necessity to interconnect political and economic problems and solve them together. As a discipline, the main objective of the international political economy is to provide a comprehensive perspective to the social phenomenon and events in world politics. Within this framework, it is argued that international system, structure, actors and events will be better understood and explained through the comprehensive perspective of the international political economy.